FILM PREPARATION OF KAPPA-CARRAGEENAN (RED SEAWEED) BIOPOLYMER AS A NATURAL ELECTROLYTE IN ORGANIC BATTERY - Komala Sari, Visi
The development of battery technology is currently quite rapid, especially in terms of improving performance by modifying the structure of the device or getting good material candidates, especially for its main components, namely electrolytes and electrodes. It is known that liquid and solid electrolytes still dominate the types of electrolytes that are currently developing. Liquid electrolytes are known to have a large conductivity value but are flammable and have a high leakage rate. Meanwhile, solid electrolytes are relatively safe with low conductivity values and are not flammable. Currently, research on electrolyte materials has been carried out, one of which is to make electrolytes from natural materials that have much potential as organic materials with conductivity comparable to conventional electrolytes. One of them is using kappa-carrageenan biopolymer which has been widely used as an electronic component. However, the physical, mechanical, and chemical characteristics of kappa-carrageenan have not been discussed in detail by researchers to date. The focus of this research is to study the preparation of kappa-carrageenan biopolymer films, analyze the characteristics of biopolymer films, and study their opportunities as electronic component materials, especially batteries. In this study, the biopolymer film is projected as an electrolyte providing ions and cations through the addition of salt, namely ammonium chloride (NH4Cl). In this study, the biopolymer film is projected as an electrolyte providing ions and cations by adding salt, namely ammonium chloride (NH4Cl). The quality of kappa carrageenan film was characterized through Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), Tensile Strength, and conductivity tests using EIS. Opportunities as an electrolyte in the battery were tested through charge and discharge characterization. Morphological test results show that the surface of kappa-carrageenan when ammonium chloride (NH4Cl) is added is smoother than the surface of pure kappa-carrageenan. XRD test results show that kappa-carrageenan containing ammonium chloride (NH4Cl) is semi-crystalline and has a high intensity with a peak around 2? = 32º. Investigation of the mechanical test results resulted in the flexibility of the film with KC and KC+NH4Cl showing the largest tensile stress value is in the KC+20wt% NH4Cl sample which is 0.2 Mpa and the elastic modulus in the KC+16.67wt% NH4Cl sample which is 2.94 Mpa greater than the KC film which is 0.086 Mpa. The EIS test results for KC with the addition of NH4Cl showed the highest film conductivity of 2.11 x 10-5 S/m, quite low compared to previous studies which reached a conductivity of 4.53x10-5 S/m. The maximum voltage for organic batteries with added salt is 3.1 V and 2.1 V for batteries without added salt through the charging process. They then tested the performance of organic batteries by adding loads in the form of LEDs and producing the highest current of 26.62 mA and the lowest of 4.55 mA for about 16 minutes to 65 minutes in the discharge process.